KINERJA PENYULUH KEHUTANAN DI KESATUAN PENGELOLAAN HUTAN (KPH) TANAH LAUT - Astri Belinda Nur Asrifa; Asysyifa Asysyifa; Hafizianor Hafizianor (Universitas Lambung Mangkurat, 2022)
The aims of this research was to analyze the level of foresty intructor performance in KPH Tanah Laut and to analyze the factors that affect the level of foresty intructor performance in KPH Tanah Laut. The research method used is saturation sampling method. Saturation sampling method is the sampling method with entire population. The data was collected by interview and distributing questionnaires as primary data and secondary data of information from journals, report or data from related intitute. The result showed that the performence of forestry intructor in KPH Tanah Laut based on an assessment of 7 criteria (Employee Administration, The Condition of Working Area, The Planning, The Forestry Conseling Activity, Result and Impact of the Forestry Conseling Activity, Monitoring, Evaluation and Reporting, and Development Activities of the Supporting Profession) overall got a “good” level of performance with score of 60,45. Meanwhile, for each respondent such as respondent 1, the performance level was